Application of multiple interactive teaching methods in clinical nursing teaching (多元互动式教学方法在临床护理教学中的应用) - WANG Shangying (王尚莹); LI Tong (李彤); LI Qingling (李庆玲); GAO Donghua (高冬华); TANG Ling (唐玲) (Association of Integrative Nursing, 2023)
Objective To evaluate the application of multiple interactive teaching methods in clinical nursing teaching and practice. Methods From August 2021 to April 2022, a total of 96 nursing students who participated in the internship in the hospital were selected as the research objects, and were randomly divided into the control group and observation group, with 48 nursing students in each group. The conventional teaching method was used in the control group, while the multiple interactive teaching method was adopted in the observation group. The theoretical knowledge, operational skills and satisfaction with different teaching methods were compared between the two groups, and the application effect of different teaching methods was comprehensively analyzed. Results Scores of theoretical knowledge test and practice skills assessment in the observation group were higher than those in the control group, with a significant difference (P＜0. 01). The score of satisfaction assessment in the observation group was higher than those in the control group, with a significant difference (P＜0. 01). Conclusion The multi-interactive teaching model can deepen the learning of theoretical knowledge and improve the comprehensive quality of nursing students. (目的 研究多元互动式教学方法在临床护理教学实践中的应用效果。方法 选取2021年8月-2022年4月在北京中医药大学东方医院实习的96名实习护生为研究对象, 随机分为两组: 对照组48名实习护生, 采用常规方法教学; 观察组48名实习护生, 接受多元互动式教学。对比两组实习护生理论知识和操作技能考核成绩, 评价实习护生对不同教学方法的满意程度, 综合分析不同教学方法的应用效果。结果 观察组护生理论知识和操作技能成绩高于对照组, 差异有统计学意义(P＜0. 01)。观察组护生对教学方法的满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 多元互动教学模式可以加深护生对理论知识的学习效果, 提升其综合素质, 教学效果明确。)